The old rules of marketing are dead 6 new rules to reinvent your brand & reignite your business - Pearson, Timothy R. (New York McGraw-Hill, 2011)
Argues that the new methods of human communication require a new perspective on marketing, outlining a plan to reinvent the marketing industry by applying quantitative data and providing leadership in a new business landscape.
Revolutionary new technologies developed over the past decade have completely changed the way humans communicate and transact business. Not exactly late-breaking news for most people of the world... except for those who are supposed to be marketing to them. While consumers, customers, and marketplaces have adapted to these new realities, most marketers have not. Renowned marketing expert Tim Pearson explains why you need to sever your ties to the comfortable old ways of marketing--and bring your company's marketing into the twenty-first century. Too many marketers still operate as if strategy necessarily depends upon predetermined budgets; advertising is the catch-all to every problem; and marketing results can't be measured. It all adds up to the age-old belief that marketing is an art, not a science--which couldn't be further from the truth. -- Publisher description.
Introduction : What Memo Did Marketers Miss? ---- I. The Core is Everything --- II. You Have Nothing Without the Foundation --- III. There are Many Choices but Only One Customer --- IV. Do the Right Things for the Right Reasons --- V. Infrastructure is More than Just Pipes --- VI. Lead and Others Will Follow --- VII. The Essence of Marketing Today ---- Conclusion: the essence of marketing today.
Includes index.
CSSP-8779, CSSP-8780 donated by The Asia Foundation Books for Asia.
Keywords: Branding (Marketing); Customer relations